Glucokinase activity in isolated islets from obese fa/fa Zucker rats. - Chan, C B (1993)
Glucokinase (EC 2.7.1.2) activity of B-cells was measured in extracted pancreatic islets isolated from lean and obese fa/fa Zucker rats and maintained in primary culture overnight. Formation of [14C]glucose phosphoric esters from D-[U-14C]glucose was measured in the presence of unlabelled glucose from 0.05 to 0.50 mM for hexokinase (EC 2.7.1.1) activity, and 8.0-16.0 mM unlabelled glucose for glucokinase activity. Eadie-Hofstee analysis revealed that hexokinase kinetic parameters (Vmax and Km) for [14C]glucose phosphoric ester formation were similar in lean- and fa/fa-rat islets. For glucokinase, there was no difference in Vmax. between phenotypes. A non-significant tendency to increased sensitivity to glucose was noted in the fa/fa-rat islets (P = 0.13). In lean-rat islets, the glucokinase inhibitor mannoheptulose (3 mM) decreased Vmax. by 80% and increased the apparent Km from 3.3 +/- 0.7 mM to 12.2 +/- 2.0 mM (P < 0.05). There was no difference in Km or Vmax. in mannoheptulose-treated versus control islets from fa/fa rats. This lack of effect was consistent with reported effects of mannoheptulose on insulin secretion from fa/fa-rat islets [Chan, MacPhail and Mitton (1993) Can. J. Physiol. Pharmacol. 71, 34-39]. The data from glucose and mannoheptulose experiments support the hypothesis that glucokinase function is altered in fa/fa Zucker rats and may contribute to fasting hyperinsulinaemia in vivo in these animals.